'Blurred boundaries': When nurses and midwives give anti-vaccination advice on Facebook. (May 2022) - Green, Janet; Petty, Julia; Whiting, Lisa; Orr, Fiona; Smart, Larissa; Brown, Ann-Marie; Jones, Linda
Background: Nurses and midwives have a professional obligation to promote health and prevent disease, and therefore they have an essential role to play in vaccination. Despite this, some nurses and midwives have been found to take an anti-vaccination stance and promulgate misinformation about vaccines, often using Facebook as a platform to do so. Research question: This article reports on one component and dataset from a larger study – 'the positives, perils and pitfalls of Facebook for nurses'. It explores the specific issue of nurses and midwives who take an anti-vaccination stance, deemed to be unprofessional by crossing professional boundaries and by providing medical information on Facebook that is not within their scope of practice. Participants: Data were collected via an online worldwide survey from nurse and midwife participants, distributed and 'snowballed' through relevant nursing and midwifery groups on Facebook. In total, 1644 Registered Nurses and Midwives, and Enrolled Nurses worldwide attempted the online survey. There were 1100 (66.9%) completed surveys and 54 partially (33.1%) completed surveys. Semi-structured interviews were also conducted online using Skype® with 17 participants in Australia. Ethical considerations: Ethical processes and procedures have been adhered to relating to privacy, confidentiality and anonymity of the participants. Findings/results: A mixed-methods approach was used, including descriptive and content analysis of the quantitative survey data and thematic analysis of the qualitative interview data. The main theme 'blurred boundaries' was generated, which comprised three sub-themes: 'follow the science, 'abuse of power and erosion of trust' and 'the moral and ethical responsibility to safeguard public health'. The results offer an important and unique understanding of how nurses and midwives interpret the conduct of fellow health professionals as unprofessional and crossing the professional boundary if they used Facebook to promulgate anti-vaccination messages and/or give medical advice online. Conclusion: There are many positives and negatives for nurses and midwives associated with using Facebook for personal and professional communication, which is in keeping with the results of the larger study from which this article is taken. Professional behaviour is a key theme in the larger research as is the ethical construct of 'every act has a consequence'; however, in this article, the theme 'blurred boundaries' offers an overall understanding of how nurses and midwives interpret the behaviour of their colleagues who espouse anti-vaccination sentiment and/or give medical advice online that is outside their scope of practice and education.